2020
DOI: 10.1101/2020.06.01.128199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robotic Assay for Drought (RoAD): An Automated Phenotyping System for Brassinosteroid and Drought Response

Abstract: Brassinosteroids (BRs) are a group of plant steroid hormones involved in regulating growth, development, and stress responses. Many components of the BR pathway have previously been identified and characterized. However, BR phenotyping experiments are typically performed on petri plates and/or in a lowthroughput manner. Additionally, the BR pathway has extensive crosstalk with drought responses, but drought experiments are time-consuming and difficult to control. Thus, we developed Robotic Assay for Drought (R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“… Xiang et al (2020) reported a robotic assay for drought (RoAD) by using a mobile cart. In this system, measurement equipment was carried by a robot, and plants were not delivered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Xiang et al (2020) reported a robotic assay for drought (RoAD) by using a mobile cart. In this system, measurement equipment was carried by a robot, and plants were not delivered.…”
Section: Discussionmentioning
confidence: 99%
“…With the function, plant pots could be automatically picked up or returned with robust behavior. Xiang et al (2020) reported a robotic assay for drought (RoAD) by using a mobile cart. In this system, measurement equipment was carried by a robot, and plants were not delivered.…”
Section: Development Of a Plant Conveyance System Using An Agvmentioning
confidence: 99%
See 1 more Smart Citation
“…BR Phenotyping Methods. BL phenotyping were carried out as previously described (58). Seeds were sterilized for 4 hours in a Nalgene Acrylic Desiccator Cabinet (Fisher Scientific, 08-642-22) by mixing 200mL bleach (8.25% sodium hypochlorite) with 8mL concentrated hydrochloric acid to generate chlorine gas.…”
Section: Mutant Bes1 Cloning and Protein Level Detectionmentioning
confidence: 99%